Thin film for photocatalytic water decomposition as well as preparation method and application of thin film
Through the layered coating technology of heterogeneous ingredients, the multi -layered thin film structure is constructed, and the range of light absorption is expanded to the entire visible light range, which solves the lack of photocatalytic water decomposition in light absorption and catalytic efficiency, and achieves high -efficiency photocatalytic moisture decomposition.
Patent Information
- Application Number
- CN202411478161.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The photocatalytic water decomposition film has shortcomings in light absorption and catalytic efficiency, especially the low utilization rate of visible light and the high recombination rate of photogenerated electrons, resulting in low efficiency.
The differential layered coating method is adopted to build a multi-layer thin film structure composed of AGBIP2SE6, AGBI1-XSBXP2SE6, Tisbp2se6, and TISB1-YBIYP2SE6 membrane layer. Through layer-by-layer coating and thermal treatment, the light absorption range is expanded to the entire visible light range.
It significantly improves the efficiency of photocatalytic water decomposition, realizes the effective use of the entire visible light range, and improves optical conversion efficiency.
Smart Images

Figure CN119346144A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic semiconductor materials, and in particular relates to a film for photocatalytic water decomposition and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Solar water splitting to produce hydrogen is an ideal method to convert solar energy into chemical energy. Although the efficiency of photocatalytic water splitting to produce hydrogen is relatively low (about 1%), its system design is simple and the cost is low, making it suitable for large-scale production.
[0004] Photocatalytic water-splitting films have potential in energy conversion and environmental governance, but face many challenges: light absorption is mainly in the ultraviolet region, and the utilization rate of visible light is low; photogenerated electrons and holes are easy to recombine, reducing the catalytic efficiency; long-term illumination or specific conditions may lead to performance degradation; the preparation cost of high-performance films is high, which hinders commercial application; the catalytic active sites are limited and there may be selectivity problems.
[0005] As a semiconductor, AgSbP2Se6 crystals in the selenophosphate phase have a certain conductivity at room temperature. Monolayer AgBiP2Se6 has a favorable energy band position suitable for water decomposition because its valence band maximum (VBM) is 0.41eV higher than the water oxidation potential, while its conduction band minimum (CBM) is 0.67eV lower than the hydrogen reduction potential. The band gap of monolayer AgBiP2Se6 is located in the visible light region, which is suitable for water decomposition reaction under visible light. Monolayer AgBiP2Se6 has out-of-plane spontaneous polarization, which can generate an electric field between the two surfaces, thereby effectively separating electrons and holes. Combined with its strong visible light adsorption ability, suitable band edge alignment and out-of-plane spontaneous polarization characteristics, monolayer AgBiP2Se6 is expected to become an excellent material for photocatalytic water decomposition.
[0006] However, the light absorption range of AgBiP2Se6 single crystal is still insufficient, resulting in low light conversion efficiency. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a thin film for photocatalytic water decomposition and its preparation method and application, and adopt a different-composition layered coating method to expand the light absorption range of AgBiP2Se6 single crystal to the entire visible light range, thereby achieving a higher light conversion efficiency.
[0008] In order to achieve the above object, the technical solution of the present invention is:
[0009] In the first aspect, a film for photocatalytic water decomposition comprises, from bottom to top: a AgBiP2Se6 film with a thickness of 60 to 70 μm, an AgBi 1-x Sb x P2Se6 film, TiSbP2Se6 film with a thickness of 50 to 60 μm, and TiSbP2Se6 film with a thickness of 45 to 55 μm 1-y Bi y P2Se6 film; 0.1≤x≤0.35, and 0.05≤y≤0.25;
[0010] Among them, AgBi 1-x Sb x In the P2Se6 film, the x value increases gradually from the bottom to the surface;
[0011] TbS 1-y Bi y In the P2Se6 film, the y value gradually increases from the bottom to the surface.
[0012] Optionally, the values of x include: 0.1, 0.25, and 0.35.
[0013] Optionally, the values of y include: 0.05, 0.15, and 0.25.
[0014] Optionally, the AgBiP2Se6 film, AgBi 1-x Sb x P2Se6 film, TiSbP2Se6 film and TiSb 1-y Bi y The P2Se6 films are single-oriented films, and the orientation direction is consistent with the thickness direction.
[0015] Optionally, the film for photocatalytic water decomposition is arranged on a substrate material, and the substrate material includes: a quartz or glass substrate.
[0016] In a second aspect, the method for preparing the above-mentioned film for photocatalytic water decomposition comprises the following steps:
[0017] S1, spin coating the AgBiP2Se6 precursor solution on the substrate material, performing heat treatment, repeating the spin coating and heat treatment 2 to 5 times, and then performing fine heat treatment to form an AgBiP2Se6 film;
[0018] S2, AgBi 1-x Sb x The precursor solution of P2Se6 is spin-coated on the AgBiP2Se6 film, and then heat-treated. After repeating the spin-coating and heat-treatment for 2 to 5 times, a fine heat treatment is performed to form AgBi 1-x Sb xP2Se6 film;
[0019] S3, spin-coat the TiSbP2Se6 precursor solution on AgBi 1-x Sb x The P2Se6 film is heat treated, and after the spin coating and heat treatment are repeated 2 to 5 times, a fine heat treatment is performed to form a TiSbP2Se6 film;
[0020] S4, TiSb 1-y Bi y The precursor solution of P2Se6 is spin-coated on the TiSbP2Se6 film, and then heat-treated. After repeating the spin-coating and heat-treatment for 2 to 5 times, a fine heat treatment is performed to form a TiSb 1-y Bi y P2Se6 film, to obtain a thin film for photocatalytic water splitting;
[0021] In S1 to S4, the heat treatment method includes: keeping at 70 to 80° C. for 10 to 15 minutes, then keeping at 90 to 110° C. for 10 to 15 minutes, and then keeping at 170 to 190° C. for 10 to 20 minutes;
[0022] The method of fine heat treatment comprises: heat treatment at 400-450° C. for 20-28 hours, and then heat treatment at 500-550° C. for 140-148 hours.
[0023] Optionally, the substrate material is pre-treated, and the pre-treatment method includes: placing the substrate material in alcohol, acetone and deionized water in turn, performing ultrasonic cleaning for 5 to 10 minutes respectively, and then blowing it dry with high-purity nitrogen.
[0024] Optionally, in S1, silver nitrate, bismuth nitrate and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.08-1.016):1:(2.00-2.16) to obtain solution A; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; solution A and selenium solution are mixed in a ratio of 1:(6.0-6.3) of the stoichiometric ratio of the solute in solution A to selenium, and the reaction is stirred for 1.5-3h to obtain a precursor solution of AgBiP2Se6.
[0025] Optionally, a set amount of ethanol is added to the mixture of solution A and selenium solution as an auxiliary solvent.
[0026] Optionally, in S1 to S4, the spin coating method includes: a rotation speed of 4200 rpm and a duration of 35 seconds.
[0027] Optionally, in S2, silver nitrate, bismuth nitrate, antimony chloride and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.008-1.020):1-x:x:(2.00-2.16) to obtain a B solution; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; the B solution and the selenium solution are mixed in a ratio of 1:(6.0-6.3) according to the stoichiometric ratio of the solute in the B solution to selenium, and the reaction is stirred for 1.5-3h to obtain AgBi 1-x Sb x A precursor solution of P2Se6, wherein 0.1≤x≤0.35.
[0028] Optionally, the values of x include: 0.1, 0.25, and 0.35.
[0029] Optionally, a set amount of ethanol is added to the mixture of solution B and selenium solution as an auxiliary solvent.
[0030] Optionally, in S2, in the order of x values from small to large, spin-coat the AgBi with the smallest x value first. 1-x Sb x The precursor solution of P2Se6 is heat treated, and after the heat treatment, AgBi with a larger x value is spin-coated 1-x Sb x The precursor solution of P2Se6 is heat treated until the AgBi 1-x Sb x Preparation of P2Se6 film.
[0031] Optionally, S3, dissolve tetrabutyl titanate, antimony chloride and ammonium dihydrogen phosphate in water in a molar ratio of (1.00-1.05):1:(2.00-2.16) to obtain a C solution; dissolve selenium in dimethyl sulfoxide to form a selenium solution; mix the C solution and the selenium solution in a stoichiometric ratio of the solute in the C solution to selenium of 1:(6.0-6.3), stir the reaction for 1.5-3h, and obtain a TiSbP2Se6 precursor solution.
[0032] Optionally, a set amount of ethanol is added to the mixture of the C solution and the selenium solution as an auxiliary solvent.
[0033] Optionally, S4, tetrabutyl titanate, antimony chloride, bismuth nitrate and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.00-1.05):(1-y):y:(2.10-2.16) to obtain a D solution; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; the D solution and the selenium solution are mixed in a stoichiometric ratio of the solute in the D solution to selenium of 1:(6.0-6.3), and the reaction is stirred for 1.5-3h to obtain TiSb 1-y Bi yA precursor solution of P2Se6, wherein 0.05≤y≤0.25.
[0034] Optionally, the values of y include: 0.05, 0.15, and 0.25.
[0035] Optionally, a set amount of ethanol is added to the mixture of the D solution and the selenium solution as an auxiliary solvent.
[0036] Optionally, in S4, the TiSb with the smallest y value is first spin-coated in the order of y values from small to large. 1-y Bi y The precursor solution of P2Se6 is heat treated, and after the heat treatment, TiSb with a larger y value is spin-coated 1-y Bi y P2Se6 precursor solution and heat treatment until TiSb 1-y Bi y Preparation of P2Se6 film.
[0037] In a third aspect, the above-mentioned film for photocatalytic water decomposition is used in photocatalytic hydrogen production, and the light absorption range includes the visible light range.
[0038] The beneficial effects of the present invention are:
[0039] 1. The present invention selects AgBi by using a different composition layered coating method. 1-x Sb x P2Se6 film, TiSbP2Se6 film and TiSb 1- y Bi y P2Se6 film is added sequentially on the surface of AgBiP2Se6 film, wherein the four films are analogs with high lattice matching, and a multilayer film with a single orientation degree can be obtained, and the light absorption range of the thin film composed of the four films for photocatalytic water decomposition includes the entire visible light range, which effectively improves the photocatalytic water decomposition efficiency.
[0040] 2. In the preparation process of the present invention, each film is repeatedly spin-coated and heat-treated to accumulate the number of layers inside the film, thereby increasing its thickness, which also helps to improve the uniformity and density of the film. After that, a refined heat treatment method is used to promote further reaction / curing of the components, ensure the stability of the film structure and optimize its performance, and finally obtain high-performance films each with the characteristics of density and single orientation. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0042] Figure 1 This is a heat treatment temperature rise curve diagram in Example 1 of the present invention.
[0043] Figure 2 This is the XRD diagram of the single crystal thin film in Example 1 of the present invention.
[0044] Figure 3 The SEM image of the cross section of the single crystal thin film of Example 1 of the present invention; wherein: 1. AgBiP2Se6 thin film layer; 2. AgBi 1-x Sb x P2Se6 thin film layer; 3. TiSbP2Se6 thin film layer; 4. TiSb1-yBiyP2Se6 thin film layer;
[0045] Figure 4 This is a diagram showing the photocatalytic results of thin films with different compositions in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0047] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0048] Example 1
[0049] A film for photocatalytic water decomposition, the preparation method comprising:
[0050] Pretreatment of substrate: select quartz substrate as the substrate material for growing single-oriented thin film, put the quartz substrate into alcohol, acetone and deionized water in turn for cleaning and drying; the cleaning method includes: ultrasonic cleaning for 5-10 minutes, and drying with high-purity N2.
[0051] S1. Dissolve silver nitrate, bismuth nitrate and ammonium dihydrogen phosphate in water at a molar ratio of 1.012:1:2.08 to obtain solution A; dissolve selenium in dimethyl sulfoxide to form a selenium solution; mix solution A and selenium solution at a stoichiometric ratio of solute and selenium in solution A of 1:6.15, add a set amount of ethanol as an auxiliary solvent, stir the reaction with a magnetic stirrer for 2 hours to obtain a precursor solution of AgBiP2Se6, wherein the volume ratio of solution A to ethanol is 1:3.5;
[0052] The precursor solution of AgBiP2Se6 was dropped onto the substrate material, and the rotation speed was set to 4200 rpm for 35 seconds to achieve uniform coating of the precursor solution, followed by heat treatment. The heating curve of the heat treatment is shown in FIG. Figure 1 As shown: heat to 75℃ and keep warm for 10min, then heat to 100℃ and keep warm for 10min, then heat to 180℃ and keep warm for 10min, then air cool to room temperature;
[0053] Repeat the spin coating-heat treatment process 2 to 5 times to build a multilayer structure;
[0054] The refined heat treatment is carried out, which is a staged heat treatment: the initial stage is 400°C and lasts for 24 hours to promote further reaction and solidification of the components; then, the temperature is raised to 520°C and maintained for 144 hours to stabilize the thin film structure and obtain a substrate material with an AgBiP2Se6 film generated on the surface.
[0055] S2, taking the values of x as 0.1, 0.25 and 0.35 respectively, dissolving silver nitrate, bismuth nitrate, antimony chloride and ammonium dihydrogen phosphate in water at a molar ratio of 1.012:1-x:x:2.08 to obtain B solutions with different x values; dissolving selenium in dimethyl sulfoxide to form a selenium solution; mixing the B solutions with different x values and the selenium solution at a ratio of 1:6.3 in the stoichiometric ratio of the solute and selenium in the B solutions with different x values, adding a set amount of ethanol as an auxiliary solvent, and reacting with magnetic stirring for 2 hours to obtain AgBi with different x values 1-x Sb x Precursor solution of P2Se6, wherein the volume ratio of solution A to ethanol solution is 1:4.8;
[0056] Take AgBi when x = 0.1 0.9 Sb 0.1 The precursor solution of P2Se6 was dropped onto the AgBiP2Se6 film of the substrate material obtained in S1, and the rotation speed was set to 4200 rpm for 35 seconds to achieve uniform coating of the film; then Figure 1 The first film structure is obtained by heat treatment with the temperature rise curve shown;
[0057] Take AgBi when x = 0.25 0.75 Sb 0.25 The precursor solution of P2Se6 was dropped onto the first thin film structure of the substrate material, and the rotation speed was set to 4200rpm for 35 seconds to achieve uniform coating of the thin film; then Figure 1 The second film structure is obtained by heat treatment with the temperature rise curve shown;
[0058] Take AgBi when x = 0.35 0.65 Sb 0.35 The precursor solution of P2Se6 was dropped onto the second thin film structure of the substrate material, and the rotation speed was set to 4200rpm for 35 seconds to achieve uniform coating of the thin film; then Figure 1 The third film structure is obtained by heat treatment with the temperature rise curve shown;
[0059] The film was subjected to a fine heat treatment: the initial stage was 400°C for 24 hours to promote further reaction and solidification of the components; the temperature was then raised to 520°C for 144 hours to stabilize the film structure, and a three-layer film structure of AgBi was obtained. 1-x Sb x P2Se6 film, and the x value gradually increases from bottom to surface.
[0060] S3, dissolving tetrabutyl titanate, antimony chloride and ammonium dihydrogen phosphate in water at a molar ratio of 1.012:1:2.08 to obtain a C solution; dissolving selenium in dimethyl sulfoxide to form a selenium solution; mixing the C solution and the selenium solution at a stoichiometric ratio of the solute in the C solution to selenium of 1:6.05, adding a set amount of ethanol as an auxiliary solvent, stirring the reaction with a magnetic stirrer for 2 hours to obtain a TiSbP2Se6 precursor solution, wherein the volume ratio of the A solution to the ethanol is: 1:4.1;
[0061] The precursor solution of TiSbP2Se6 is dropped onto AgBi 1-x Sb x On the P2Se6 film, the rotation speed was set to 4200 rpm for 35 seconds to achieve uniform coating of the precursor solution, and then heat treatment was performed. The heating curve of the heat treatment is as follows: Figure 1 As shown: heat to 75℃ and keep warm for 10min, then heat to 100℃ and keep warm for 10min, then heat to 180℃ and keep warm for 10min, then air cool to room temperature;
[0062] Repeat the spin coating-heat treatment process 2 to 5 times to build a multilayer structure;
[0063] The refined heat treatment is carried out, which is a staged heat treatment: the initial stage is 400°C and lasts for 24 hours to promote further reaction and solidification of the components; then the temperature is raised to 520°C and maintained for 144 hours to stabilize the film structure and obtain a surface TiSbP2Se6 film.
[0064] S4, taking the values of y as 0.05, 0.15 and 0.25 respectively, dissolving tetrabutyl titanate, antimony chloride, bismuth nitrate and ammonium dihydrogen phosphate in water at a molar ratio of 1.02:1-y:y:2.12 to obtain D solutions with different y values; dissolving selenium in dimethyl sulfoxide to form a selenium solution; mixing the D solutions with different y values and the selenium solution at a stoichiometric ratio of the solute and selenium in the D solutions with different y values of 1:6.25, adding a set amount of ethanol as an auxiliary solvent, and reacting with magnetic stirring for 2 hours to obtain TiSb with different y values 1-y Bi y Precursor solution of P2Se6, wherein the volume ratio of solution A to ethanol solution is 1:5.2;
[0065] Take TiSb when y = 0.05 0.95 Bi 0.05 The precursor solution of P2Se6 was dropped onto the TiSbP2Se6 film obtained in S3, and the rotation speed was set to 4200 rpm for 35 seconds to achieve uniform coating of the film; then Figure 1 The temperature rise curve shown in the figure is heat treated to obtain the first layer of film structure;
[0066] Take TiSb when x = 0.15 0.85 Bi 0.15 The precursor solution of P2Se6 was dropped onto the first layer of the substrate material thin film structure, and the rotation speed was set to 4200rpm for 35 seconds to achieve uniform coating of the thin film; then Figure 1 The second layer of film structure is obtained by heat treatment with the heating curve shown in the figure;
[0067] Take TiSb when x = 0.25 0.75 Bi 0.25 The precursor solution of P2Se6 was dropped onto the second layer of the substrate material, and the rotation speed was set to 4200rpm for 35 seconds to achieve uniform coating of the film; then Figure 1 The temperature rise curve shown in the figure is heat treated to obtain the third layer of film structure;
[0068] The heat treatment was carried out at 400℃ for 24 hours to promote the further reaction and solidification of the components. The temperature was then raised to 520℃ for 144 hours to stabilize the film structure. The TiSb film with three layers was obtained. 1-y Biy P2Se6 film, and the y value gradually increases from bottom to surface.
[0069] Through the above steps, a film for photocatalytic water decomposition was obtained, and then characterized:
[0070] Film composition and orientation characterization
[0071] In order to further explore the crystal phase structure and elemental composition of the multilayer film, we used a Bruker D8 X-ray diffractometer, specifically a CuKα radiation source with a wavelength accurate to 0.15406 nanometers. Figure 2 The XRD patterns of the prepared multilayer films are shown. This result shows that the prepared multilayer films are composed of their respective pure phases and that the preferred orientation of each film layer is good.
[0072] Thin film structure thickness characterization
[0073] The cross-section of the coating deposited on the Si wafer was examined using a scanning electron microscope (SEM, model Hitachi S-4800). Figure 3 It can be clearly seen that the actual structure is consistent with the design. In the figure, 1, 2, 3, and 4 represent AgBiP2Se6, AgBi 1-x Sb x P2Se6, TiSbP2Se6 and TiSb 1-y Bi y P2Se6 thin film layer. This embodiment prepares a thin film for photocatalytic water decomposition, which includes from bottom to top: a 60μm thick AgBiP2Se6 film, a 68μm thick AgBi 1- x Sb x P2Se6 film, TiSbP2Se6 film with a thickness of 52μm and TiSb 1-y Bi y P2Se6 film. From the clear display of the cross-section, it can be clearly observed that the nano energetic film has a well-defined, uniform and tightly bonded interlayer structure, which strongly suggests that excellent adhesion is formed between the film and the substrate during the sputtering deposition process.
[0074] The absorption coefficient and energy gap of the prepared multilayer films were determined by the Tauc method. Figure 4 Shown as (αhν) 2 The relationship between the photon energy and the photon energy (hν). In the visible light region, the absorption coefficient exceeds 10 4 cm -1 Therefore, very thin nano Cu3VS4 films can absorb solar energy very effectively. AgBiP2Se6 films, AgBi1-x Sb x P2Se6 film, TiSbP2Se6 film and TiSb 1-y Bi y The band gaps of P2Se6 films are 1.75eV, 2.02eV, 2.32eV and 2.70eV, respectively, which are close to the band gaps of ideal light absorption layer materials.
[0075] Photocatalytic testing, including the following:
[0076] First, prepare the substrate according to the substrate pretreatment method of this embodiment.
[0077] Then, according to step S1 in this embodiment, a AgBiP2Se6 film is prepared on the substrate as the bottom film;
[0078] According to step S2 of this embodiment, a three-layer thin film structure of AgBi is prepared on a substrate. 1-x Sb x P2Se6 film, which is the first intermediate layer film;
[0079] According to step S3 of this embodiment, a TiSbP2Se6 film is prepared on the substrate as the second intermediate layer film.
[0080] According to step S4 in this embodiment, a TiSb1-yBiyP2Se6 film including a three-layer thin film structure is prepared on the substrate as a surface thin film.
[0081] Test results such as Figure 4 As shown, the bandgap widths (Eg) of these films are set to 1.75eV, 2.02eV, 2.32eV and 2.7eV, respectively, forming a continuous spectrum from low to high. Considering that the photon energy range of visible light roughly corresponds to the spectral interval of wavelengths from 400nm (about 3.1eV) to 700nm (about 1.77eV), it is worth noting that although a single layer of film cannot completely cover this entire visible spectrum range (because the lowest energy of visible light is slightly higher than the film with the narrowest bandgap), the cleverly designed four-layer film structure in this example, through its unique bandgap width, achieves effective coverage of the entire visible spectrum region from longer wavelengths (red and orange light region) to shorter wavelengths (blue and purple light region). This synergistic effect enables the entire film system to fully utilize and respond to the photon energy in the entire visible light range.
[0082] Furthermore, the structure of the multilayer film may also trigger a series of favorable physical effects, such as interface effects, multiple reflections and scattering of light between layers, etc. These effects jointly promote the residence time and absorption efficiency of light in the film system, thereby significantly improving the overall photocatalytic performance.
[0083] Comparative Example
[0084] Synthesis of ZnIn2S4 (ZIS for short)
[0085] (Xin,
[0086] First, 1mmol of ZnCl2, 2mmol of In(NO3)3 and 4mmol of thioacetamide were accurately measured and fully dissolved in 35mL of deionized water. Stir vigorously for 30 minutes to ensure that all components were mixed evenly and completely dissolved. After that, the mixed solution was carefully transferred to a 50mL polytetrafluoroethylene-lined autoclave, sealed and placed in a heating device, and heated at 180℃ for 12 hours to promote the thorough chemical reaction. When the reaction system is naturally cooled to room temperature, a clear yellow suspension will be observed. Next, a series of meticulous post-treatment steps are used to purify the product: first, the solid phase product is collected by filtration; then, it is thoroughly washed four times with ethanol and deionized water respectively to effectively remove impurities attached to the surface of the product and raw materials that do not participate in the reaction; finally, the cleaned product is placed in a constant temperature drying oven at 60℃ and dried to obtain the ZnIn2S4 precursor.
[0087] The ZnIn2S4 precursor was placed in a closed environment filled with Ar / H2 mixed gas (maintained at 1 atmosphere) and heated to 500°C for 30 minutes. After the heating reaction, the powder was naturally cooled to room temperature. Subsequently, ethanol and deionized water were used for multiple washings to completely remove surface residues. Finally, the product was dried at 60°C overnight in a vacuum environment to completely remove the residual solvent.
[0088] Example 2
[0089] The thin film for photocatalytic water decomposition prepared in Example 1 and the photocatalyst prepared in the comparative example were respectively used to carry out photocatalytic overall water decomposition reaction tests.
[0090] Using a reaction container with a gas closed circulation and evacuation system, before the reaction, the 20 mm × 20 mm film prepared in Example 1 and 35 milligrams (mg) of the photocatalyst prepared in the comparative example were placed in the reaction container respectively, and 50 mL of pure water was added to allow the film to contact the pure water; then the air in the container was evacuated and replaced with argon.
[0091] The film and water in the container were irradiated with a xenon lamp to undergo photocatalytic hydrogen and oxygen production reactions. The generated gas was extracted and detected by a Shimadzu GC-2014c gas chromatograph with a thermal conductivity detector.
[0092] The STH (solar energy conversion to hydrogen) efficiency was measured under simulated sunlight AM1.5 G illumination conditions (100 mW / cm2). The STH efficiency is determined by the following formula:
[0093] STH(%)=(R(H2)×ΔGr) / (P×S)×100%;
[0094] Where R(H2) represents the yield of H2; ΔGr is the reaction Gibbs free energy of the water decomposition reaction, which is set to 237 kJ / mol for liquid water in the reaction system; P is the light energy flux under AM1.5 G irradiation, which is set to 100 mW / cm2; S represents the area of the irradiated sample, which is 3.6 cm2.
[0095] According to measurement, the STH efficiency of the thin film in Example 1 is about 0.97%, and the STH efficiency of the thin film in the comparative example is about 0.57%.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A film for photocatalytic water decomposition, characterized in that: From bottom to top, it includes: AgBiP2Se6 film with a thickness of 60-70μm, AgBi 1-x Sb x P2Se6 film, TiSbP2Se6 film with a thickness of 50 to 60 μm, and TiSbP2Se6 film with a thickness of 45 to 55 μm 1-y Bi y P2Se6 film; 0.1≤x≤0.35, and 0.05≤y≤0.25; Among them, AgBi 1-x Sb x In the P2Se6 film, the x value increases gradually from the bottom to the surface; TbS 1-y Bi y In the P2Se6 film, the y value gradually increases from the bottom to the surface.
2. The film for photocatalytic water decomposition according to claim 1, characterized in that: The values of x include: 0.1, 0.25 and 0.35; optionally, the values of y include: 0.05, 0.15 and 0.
25.
3. The film for photocatalytic water decomposition according to claim 1, characterized in that: The AgBiP2Se6 film, AgBi 1- x Sb x P2Se6 film, TiSbP2Se6 film and TiSb 1-y Bi y The P2Se6 films are single-oriented films, and the orientation direction is consistent with the thickness direction.
4. The film for photocatalytic water decomposition according to claim 1, characterized in that: The film for photocatalytic water decomposition is arranged on a substrate material, and the substrate material comprises: a quartz or glass substrate.
5. A method for preparing a film for photocatalytic water decomposition as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1, spin coating the AgBiP2Se6 precursor solution on the substrate material, performing heat treatment, repeating the spin coating and heat treatment 2 to 5 times, and then performing fine heat treatment to form an AgBiP2Se6 film; S2, AgBi 1-x Sb x The precursor solution of P2Se6 is spin-coated on the AgBiP2Se6 film, and then heat-treated. After repeating the spin-coating and heat-treatment for 2 to 5 times, a fine heat treatment is performed to form AgBi 1-x Sb x P2Se6 film; S3, spin-coat the TiSbP2Se6 precursor solution on AgBi 1-x Sb x The P2Se6 film is heat treated, and after the spin coating and heat treatment are repeated 2 to 5 times, a fine heat treatment is performed to form a TiSbP2Se6 film; S4, TiSb 1-y Bi y The precursor solution of P2Se6 is spin-coated on the TiSbP2Se6 film, and then heat-treated. After repeating the spin-coating and heat-treatment for 2 to 5 times, a fine heat treatment is performed to form a TiSbP2Se6 film. 1-y Bi y P2Se6 film, to obtain a thin film for photocatalytic water splitting; In S1 to S4, the heat treatment method includes: keeping at 70 to 80° C. for 10 to 15 minutes, then keeping at 90 to 110° C. for 10 to 15 minutes, and then keeping at 170 to 190° C. for 10 to 20 minutes; The method of fine heat treatment comprises: heat treatment at 400-450° C. for 20-28 hours, and then heat treatment at 500-550° C. for 140-148 hours.
6. The method for preparing a film for photocatalytic water decomposition according to claim 5, characterized in that: The substrate material is pre-treated, and the pre-treatment method includes: placing the substrate material in alcohol, acetone and deionized water in turn, performing ultrasonic cleaning for 5 to 10 minutes respectively, and then drying with high-purity nitrogen; Optionally, the spin coating method includes: a spinning speed of 4200 rpm and a duration of 35 seconds.
7. The method for preparing a film for photocatalytic water decomposition according to claim 5, characterized in that: In S1, silver nitrate, bismuth nitrate and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.08-1.016):1:(2.00-2.16) to obtain solution A; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; solution A and selenium solution are mixed in a ratio of 1:(6.0-6.3) in which the stoichiometric ratio of the solute in solution A to selenium is 1, and the reaction is stirred for 1.5-3h to obtain a precursor solution of AgBiP2Se6.
8. The method for preparing a film for photocatalytic water decomposition according to claim 5, characterized in that: In S2, silver nitrate, bismuth nitrate, antimony chloride and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.008-1.020):1-x:x:(2.00-2.16) to obtain solution B; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; solution B and selenium solution are mixed in a ratio of 1:(6.0-6.3) according to the stoichiometric ratio of the solute in solution B to selenium, and the reaction is stirred for 1.5-3h to obtain AgBi 1- x Sb x Precursor solution of P2Se6, wherein 0.1≤x≤0.35; Optionally, in S2, in the order of x values from small to large, spin-coat the AgBi with the smallest x value first. 1-x Sb x The precursor solution of P2Se6 is heat treated, and after the heat treatment, AgBi with a larger x value is spin-coated 1-x Sb x The precursor solution of P2Se6 is heat treated until the AgBi 1-x Sb x Preparation of P2Se6 film.
9. The method for preparing a film for photocatalytic water decomposition according to claim 5, characterized in that: S3, dissolving tetrabutyl titanate, antimony chloride and ammonium dihydrogen phosphate in water at a molar ratio of (1.00-1.05):1:(2.00-2.16) to obtain a C solution; dissolving selenium in dimethyl sulfoxide to form a selenium solution; mixing the C solution and the selenium solution at a stoichiometric ratio of the solute in the C solution to selenium of 1:(6.0-6.3), stirring the reaction for 1.5-3h, and obtaining a precursor solution of TiSbP2Se6; Optionally, S4, tetrabutyl titanate, antimony chloride, bismuth nitrate and ammonium dihydrogen phosphate are dissolved in water in a molar ratio of (1.00-1.05):(1-y):y:(2.10-2.16) to obtain a D solution; selenium is dissolved in dimethyl sulfoxide to form a selenium solution; the D solution and the selenium solution are mixed in a stoichiometric ratio of the solute in the D solution to selenium of 1:(6.0-6.3), and the reaction is stirred for 1.5-3h to obtain TiSb 1-y Bi y Precursor solution of P2Se6, wherein 0.05≤y≤0.25; Optionally, in S4, the TiSb with the smallest y value is first spin-coated in the order of y values from small to large. 1-y Bi y The precursor solution of P2Se6 is heat treated, and after the heat treatment, TiSb with a larger y value is spin-coated 1-y Bi y P2Se6 precursor solution and heat treated until TiSb 1-y Bi y Preparation of P2Se6 film.
10. Use of the film for photocatalytic water decomposition according to any one of claims 1 to 4 in photocatalytic hydrogen production, characterized in that: The light absorption range includes the visible light range.